Development Strategies for New Rivermoon Ecotourism in Karanglo Village, Polanharjo District, Klaten Regency - Saipullah Hasan; Eka Wulandari; Pudji Rahmawati (UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines the development of New Rivermoon ecotourism in Karanglo Village and community participation, using Buhalis' 6A tourism development theory. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation. Informants included the head of Karanglo, New Rivermoon managers, admins, and guides. Data analysis involved reduction, presentation, and conclusion drawing, with triangulation for validation. The findings show that New Rivermoon ecotourism applies the 6A components: attraction, accessibilities, amenities, accommodation, activities, and ancillary services. This approach has successfully increased visitors, from 800 on weekdays to 1,500 on weekends. Local community participation is seen in maintaining the river’s cleanliness and sustainability, as well as in tourism management, including administration, tubing guides, cleaning staff, and parking attendants